Modelling Dynamic Relationships between Foreign Direct Investment and Intra-industry Trade in Poland - Salamaga, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
In the economic literature there are numerous theories explaining the relationship between the inflow of foreign direct investment (FDI) and foreign trade. The most frequently discussed issue is whether direct investment strengthens or restricts foreign trade. Similar questions can be formulated with regard to direct foreign investment and intra-industry trade and its types: vertical and horizontal intra-industry trade. The relationships between these variables are relatively rarely studied, but they can provide additional insights into the influence of FDI on the structure and competitiveness of foreign trade. The paper proposes to examine the relationship between FDI and different types of intra-industry trade using the vector error correction model (VECM). To investigate the feedback between these variables, the results of the impulse response functions and forecast error variance decomposition are analysed. The results will be presented using the example of Poland.